Tyrosine-phosphorylated bacterial effector proteins: The enemies within - Backert, Steffen; Selbach, Matthias (Trends in Microbiology, 2005)
The tyrosine phosphorylation of proteins has a central role during signal transduction in eukaryotes. Recent progress shows that tyrosine phosphorylation is also a common feature of several effector proteins translocated by bacterial type III and type IV secretion systems. The involvement of these secretion systems in disease development is exemplified by a variety of pathogenic processes: pedestal formation (Tir of EPEC and Citrobacter), cell scattering (CagA of Helicobacter), invasion (Tarp of Chlamydia) and possibly proinflammatory responses and cell proliferation (BepD-F of Bartonella). The discovery that different bacterial pathogens use this common strategy to subvert host-cell function suggests that more examples will soon emerge. © 2005 Elsevier Ltd. All rights reserved.
Created from Fastlane, Scopus look-up